Analysis of the migration attractiveness of the Altai Republic, Tuva and Khakassia - Oydup, Tana M.; Troshkina, Irina N.; Dilekova, Suraya D. (The New Research of Tuva, 2025)
The article presents a comparative analysis of the migration attractiveness of the republics in the Siberian Federal District — Altai, Tuva, and Khakassia. The persistence of migration outflow and high migration sentiments among high school graduates indicate that these republics are becoming unattractive for residence. This fact is primarily determined by indicators related to housing conditions, income levels, the state of the labor market, and the development of the social sphere.Based on statistical data and using correlation and cluster analysis, the factors influencing migration growth were identified. When choosing a region for potential relocation, four factors are considered as benchmarks: housing, wage levels, availability of jobs, and social infrastructure. The combination of these factors enhances the migration attractiveness of the region. In the Siberian Federal District, regions are distributed into three clusters depending on the level of migration attractiveness. The republics of Southern Siberia are grouped into the third cluster, characterized by low migration attractiveness.Khakassia is in the most favorable position, where a number of indicators exceed the average levels for Southern Siberia, while there is a need to increase per capita income, gross regional product, volume of shipped domestic products, and capital assets in the economy. In the Republics of Altai and Tuva, the range of indicators should be expanded across all directions.
Keywords: migration attractiveness; Southern Siberia; Tuva; Altai; Khakassia; migration